Diagnostic and Therapeutic Potential of microRNAs in Acute Kidney Injury - Brandenburger, Timo; Lorenzen, Johan M. (Frontiers in Pharmacology, 2020)
During hospital stay, about 20 % of adult patients experience an episode of acute kidney injury (AKI), which is characterized by a rapid decrease in glomerular filtration. Diagnostic tools especially regarding early diagnosis of kidney dysfunction prior to AKI and markers of renal recovery are not available. Additionally there is no therapeutic option for the treatment of AKI. Thus better and more specific diagnostic and therapeutic options are urgently needed in daily clinical practice. NoncodingRNAs (ncRNAs) have come into focus of research in the context of AKI in the last decade. The best characterized group of ncRNAs are microRNAs (miRNAs). An increasing body of literature has shown that miRNAs are involved in the pathogenesis of AKI and that they are promising future tools in the diagnosis and therapy of AKI. However, there are obstacles to be overcome before miRNAs can be transferred to patient care. This review will give an overview of our current knowledge of miRNA involvement in the context of AKI while critically evaluating their diagnostic and therapeutic potential.